Tyrosine kinase inhibitor, masitinib, limits neuronal damage, as measured by serum neurofilament light chain concentration in a model of neuroimmune-driven neurodegenerative disease. - Olivier Hermine; Laurent Gros; Truong-An Tran; Lamya Loussaief; Kathleen Flosseau; Alain Moussy; Colin D Mansfield; Patrick Vermersch (PLoS ONE)
Background Masitinib is an orally administered tyrosine kinase inhibitor that targets activated cells of the innate neuroimmune system. We have studied the neuroprotective action of masitinib on the manifestations of experimental autoimmune encephalitis (EAE) induced axonal and neuronal damage. EAE is a model of neuroimmune-driven chronic neuroinflammation and therefore highly relevant to masitinib's mechanism of action in neurodegenerative diseases. Importantly, neuronal damage, or prevention thereof, can be rapidly assessed by measuring serum neurofilament light chain (NfL) concentration in EAE-induced mice. Methods EAE induction was performed in healthy female C57BL/6 mice via active MOG 35-55 peptide immunization. Treatments were initiated 14 days post EAE induction. On day-0, 39 mice with established EAE symptoms were randomly assigned to 3 treatment groups (n = 13): EAE control, masitinib 50 mg/kg/day (M50), and masitinib 100 mg/kg/day (M100). The treatment started on day-1 and ended on day-15. Blood samples were collected on day-1 and day-8, via tail vein sampling, and on day-15, via intracardiac puncture. Assessments included quantification of serum NfL levels along the disease duration, cytokine quantification at day-15, and clinical assessments. Results Masitinib treatment significantly (p < 0.0001) limited NfL production with respect to control; specifically, relative change in serum NfL concentration at day-8 was 43% and 60% lower for the M50 and M100 groups, respectively. Likewise, for the assessment of absolute serum NfL at day-8 and day-15, there was a significantly lower NfL concentration for masitinib treatment as compared with control. Furthermore, EAE mice treated with masitinib showed significantly lower concentrations of several well-established pro-inflammatory cytokines relative to control at day-15. A beneficial effect of masitinib on functional performance was also observed, with both M50 and M100 groups showing significantly less relative deterioration in grip strength at day-15 as compared with control (p < 0.001). Conclusion This study is the first demonstration that masitinib, a drug that targets the innate as opposed to the adaptive neuroimmune system, can lower serum NfL levels, and by extension therefore, neuronal damage, in a neuroimmune-driven neurodegenerative disease model. Overall, findings indicate that masitinib has a neuroprotective effect under conditions of chronic neuroinflammation and therefore plausible disease-modifying activity across a broad range of neurodegenerative diseases.